The Prescription Pattern of Acetaminophen and Non-Steroidal Anti-Inflammatory Drugs in Patients with Liver Cirrhosis - Hong, Young Mi; Yoon, Ki Tae; Heo, Jeong; Woo, Hyun Young; Lim, Won; An, Dae Seong; Han, Jun Hee; Cho, Mong (Journal of Korean medical science, 2016)
Analgesics, known to be hepatotoxic drugs, are frequently prescribed to patients with liver cirrhosis who are prone to drug-induced liver injury. No guidelines are available regarding the prescription of analgesics in these patients. Therefore, we aimed to evaluate the prescription pattern of most frequently used analgesics in patients with cirrhosis. We assessed the prescription pattern of acetaminophen and non-steroidal anti-inflammatory drugs (NSAIDs) in patients with liver cirrhosis registered in Health Insurance Review Assessment Service database between January 1, 2012 and December 31, 2012. A total of 125,505 patients with liver cirrhosis were registered from January 1, 2012 to December 31, 2012. Of that group, 50,798 (40.5%) patients claimed reimbursement for at least one prescription for acetaminophen or NSAIDs during the one year follow-up period. Overall, NSAIDs (82.7%) were more prescribed than acetaminophen (64.5%). NSAIDs were more prescribed than acetaminophen even in decompensated cirrhosis compared with compensated cirrhosis (71.5% vs. 68.8%, P value < 0.001). There was a marked difference in prescription preference between acetaminophen and NSAIDs among physicians. Internists more frequently prescribed acetaminophen than NSAIDs compared to other physicians (50.9% vs. 76.2%, P < 0.001). Gastroenterologists more frequently prescribed acetaminophen over NSAIDs compared to other internists (80.9% vs. 51.2%, P < 0.001). Analgesics were prescribed in 40.5% of patients with cirrhosis. NSAIDs were more frequently prescribed although they should be avoided. The prescription pattern of analgesics were different significantly among physicians in patients with liver cirrhosis. The harmful effects of NSAIDs in patients with cirrhosis should be reminded to all physicians prescribing analgesics.